2002
DOI: 10.4049/jimmunol.168.11.5465
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles for CD19 and Bruton’s Tyrosine Kinase in B Lymphocyte Signal Transduction

Abstract: CD19 and Bruton’s tyrosine kinase (Btk) may function along common signaling pathways in regulating intrinsic and B cell Ag receptor (BCR)-induced signals. To identify physical and functional interactions between CD19 and Btk, a CD19-negative variant of the A20 B cell line was isolated, and CD19-deficient (CD19−/−) and CD19-overexpressing mice with the X-linked immunodeficient (Xid; Btk) mutation were generated. In A20 cells, Btk physically associated with CD19 following BCR engagement. CD19 and Btk interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
5
30
1
Order By: Relevance
“…One known mechanism of its action is the recruitment and activation of PI3 and subsequently Akt kinases (38)(39)(40)(41)(42). This is accomplished through the docking function of 2 tyrosine residues, Y482 and Y513, in the cytoplasmic region of CD19 (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One known mechanism of its action is the recruitment and activation of PI3 and subsequently Akt kinases (38)(39)(40)(41)(42). This is accomplished through the docking function of 2 tyrosine residues, Y482 and Y513, in the cytoplasmic region of CD19 (60).…”
Section: Discussionmentioning
confidence: 99%
“…One of the known functions of CD19 signaling is the recruitment and activation of PI3K (38) and ensuing activation of Akt (39)(40)(41)(42), all in the context of BCR signaling (reviewed in ref. 43).…”
Section: Pax5 Sustains C-myc Protein Levelsmentioning
confidence: 99%
“…Another group using dominant-negative mutant of Syk did not obtain similar result, suggesting that this mutant did not completely inhibit Syk function in A20 cells (11). During preparation of manuscript, it was reported that BCRinduced phosphorylation of Akt is not reduced in the absence of CD19 (20), suggesting that the Syk-dependent recruitment of PI3K to CD19, as seen in Fig. 5B, might not play a central role in the BCR-induced PI3K activation.…”
Section: Discussionmentioning
confidence: 89%
“…For example, BCR-mediated activations of ERK, JNK, and p38 MAPKs are almost lost in BLNK-deficient DT40 cells (13), but nearly intact in BLNK-deficient mouse B cells (30). BLNK or Btk deficiency results in complete loss of BCR-induced calcium mobilization in DT40 cells (13,41), but partial or slight impairment in mouse B cells (20,33,(42)(43)(44). It is possible that DT40 cells lack a Syk-independent pathway(s) for BCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…49 A recent paper claims that TLR9 and BCR cosignaling also depend on BTK, which is essential for the colocalization of BCR and TLR9. 32 Taking all of these results together, we suggest that in the case of BCR-CD19 crosslinking by anti-IgG and XENP6187, BTK is exhausted by CD19 and is not available for BCR-TLR9-induced synergistic signaling.…”
Section: Discussionmentioning
confidence: 99%